A synthetic quality index to evaluate the functional stability of soil microbial communities after perturbations - E. Picariello (Elsevier, 2021)
Soil stability includes both resistance, the ability to withstand a perturbation or stress, and resilience, the ability to recover to pre perturbation levels. The functional stability of soil microbial communities is of paramount importance for the ecosystem functioning. We investigated the differences in the stability (resistance and resilience) of three enzyme activities (hydrolytic, laccase and peroxidase) in three different forest (holm oak, black pine and beech) soils after addition of PAHs (phenanthrene, pyrene and benzo[a]pyrene) with different molecular weights. Furthermore, we proposed a new soil quality index (MAI) based on the measured enzyme activity values, useful to quantify the ecological impact of soil perturbations (PAH exposure in our case).The degradation rates of different PAHs follow their complexity, slowing with increasing of PAH molecular weight in all soil types. Moreover, we found higher microbial resistance to PAH perturbation in “broad scale” enzyme activity (hydrolase), in respect to the two “narrow-niche” enzyme activities (laccase and peroxidase). The results demonstrate a higher functional stability in soils with a higher content of recalcitrant organic matter (soil under pine), compared to soils with higher content of labile organic matter (soil under holm oak). In particular, laccase activity is less affected by phenanthrene and pyrene addition in soil under pine; peroxidase activity shows a higher resistance and resilience in soil under beech for all PAHs added. Resistance and/or resilience to PAH contamination, observed for hydrolytic functional stability in the three soils, is mainly due to the high diversity of enzymes expressing this type of catalytic activity.